2015
DOI: 10.5551/jat.26161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Body Mass Index on the Lipid Profile and Biomarkers of Inflammation and a Fibrinolytic and Prothrombotic State

Abstract: Aim:Both an overweight status and obesity are associated with high cardiovascular morbidity and mortality. The aim of this study was to examine the effects of obesity on different underlying mechanisms, i.e. inflammation, fibrinolysis and a prothrombotic state, in a young high-risk population in the Mediterranean area. Methods: The study population included 237 subjects (median age: 44 years). We recorded the presence of cardiovascular risk factors and premature ischaemic heart disease and performed weight str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 44 publications
0
12
0
5
Order By: Relevance
“…In this study, human genetic evidence supports a causal role for obesity in risk for VTE. Recent work has suggested that the pro-inflammatory state induced by obesity may result in impaired fibrinolysis and an increased risk of VTE 51 . As such, therapies targeting the obesity epidemic to reduce the burden of cardiometabolic disease may also mitigate the rising incidence of VTE events 44 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, human genetic evidence supports a causal role for obesity in risk for VTE. Recent work has suggested that the pro-inflammatory state induced by obesity may result in impaired fibrinolysis and an increased risk of VTE 51 . As such, therapies targeting the obesity epidemic to reduce the burden of cardiometabolic disease may also mitigate the rising incidence of VTE events 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, D-dimer was not associated with obesity in a cohort of uninfected participants. 33 These studies, which did not compare HIV+ with uninfected participants in the same cohort, have limited ability to comment on the differential impact of obesity on these biomarkers in those living with HIV versus without HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…These three biomarkers were chosen because they represent different inflammatory pathways, and are altered in the context of HIV and obesity. 23,30-33 …”
Section: Introductionmentioning
confidence: 99%
“…These results were in contrast with some previous literature studies, 11,[49][50][51][52] which reported the influence of such parameters on endothelial function and on vascular wall morphological structure. In fact, OrenesPiñero et al 53) pointed out the correlation between BMI and coagulation parameters, observing an increased prothrombotic status in adult subjects suffering from increased body weight.…”
Section: Discussionmentioning
confidence: 99%